The Effect of Convective Injection of Ice on Stratospheric Water Vapor in a Changing Climate. Issue 9 (2nd May 2022) - Smith, Jacob W.; Bushell, Andrew C.; Butchart, Neal; Haynes, Peter H.; Maycock, Amanda C.
Abstract: Stratospheric water vapor affects the Earth's radiative balance and stratospheric chemistry, yet its future changes are uncertain and not fully understood. The influence of deep convection on stratospheric water vapor remains subject to debate. This letter presents a detailed process‐based model study of the impact of convective ice sublimation on stratospheric water vapor in response to CO2 forced climate change. The influence of convective injection is found to be limited by the vertical profile of temperature and saturation vapor pressure in the tropical tropopause layer, not by the frequency of occurrence. Lagrangian trajectory analysis shows the relative contributions to stratospheric water vapor from sublimation and large‐scale transport are approximately unchanged when CO2 is increased. The results indicate the role of convective ice injection for stratospheric water vapor in a warmer climate remains constrained by large‐scale temperatures. Plain Language Summary: Trends in stratospheric water vapor impact on both ozone depletion and the climate. Water vapor enters the stratosphere in the tropics and is tightly constrained by the cold temperatures around the tropopause (around 15–17 km altitude). For the present day climate the contribution from the direct injection of ice into the stratosphere by deep convection is thought to be relatively small, but it has been suggested these may increase in a warmer climate. If convection becomes more frequent and stronger under greenhouse gas induced climate change, the response of stratospheric water vapor might be different from that implied simply by changes to tropical tropopause temperatures. This study examines the roles of convection and large‐scale temperatures and transport in determining the water budget in the tropical tropopause region in a climate model. In response to increased atmospheric carbon dioxide the model simulates increased stratospheric water vapor with a substantial contribution coming from more convective injection. However, the relative contribution of convective injection to stratospheric water vapor remains roughly constant as carbon dioxide increases. Therefore, irrespective of whether convection becomes stronger or more frequent, the impact of convective injection of water is found to be constrained by large‐scale temperatures. Key Points: We present an innovative method to quantify the processes that lead to a modeled increase in stratospheric water vapor from increased CO2 As well as changes in large‐scale temperatures and transport, we find convective injection of ice contributes to stratospheric moistening The frequency of convective injection increases as CO2 increases, but its relative contribution to stratospheric water vapor does not